THE APPLICATION OF THE PROJECT BASED LEARNING MODEL IN INCREASING STUDENT ENTREPRENEURIAL MOTIVATION IN HIGHER EDUCATION - Mantasia; Purnamawati; Nur, Hasanah (Pascasarjana Universitas Negeri Makassar, 2023)
This study aimsto: (1) determine the application of the Project Based Learning model in increasing entrepreneurial motivation for students of Electronic Engineering Education, Faculty of Engineering, UNM; (2) to find out how much the entrepreneurship motivation of students of the Electronics Engineering Education Faculty of Engineering, UNM; (3) to determine the effect of the Project Based Learning model on increasing the entrepreneurial motivation of students. This research is a quantitative research, with a survey research type.The data collection technique used a questionnaire, while the data analysis method used a percentage descriptive analysis in the form of simple linear regression. The research results obtained are: one, the application of the Project Based Learning model is in the very good category with an average value of 86%; two, Entrepreneurial motivation of students of the Electronics Engineering Education Faculty of Engineering UNM is in the high category with an average score of 80%; three, the Project Based Learning model has a positive effect on increasing entrepreneurial motivation by 80%.